Face Flow: Constrained Optical Flow Framework for Faces - Alkaddour, Muhannad (2020)
A Master of Science thesis in Mechatronics Engineering by Muhannad Alkaddour entitled, “Face Flow: Constrained Optical Flow Framework for Faces”, submitted in May 2020. Thesis advisors are Dr. Usman Tariq and Dr. Abhinav Dhall. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).